Risk assessment and juvenile justice: an interaction between risk, race, and gender - Campbell, Christina A. (Criminology & public policy, 2018)
In this study, we examine the interaction between race, gender, and risk assessment score on risk for recidivism. We used the Youth Level of Service/Case Management Inventory (YLS/CMI) to measure criminogenic risk among a sample of delinquent youth. The results of multivariate Cox regression revealed a significant interaction between race, gender, and risk score when predicting recidivism. The findings indicated that the slope of the relationship between risk score and recidivism differed significantly for Black youth as compared with White youth and that this interaction was even more pronounced for the subsample of males. These findings suggest that there may be social or other policy/enforcement‐related factors that increase risk for recidivism for Black youth.